2009
DOI: 10.1093/molehr/gap076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of highly purified urinary FSH and human menopausal FSH on uterine myoelectrical dynamics

Abstract: The aim of the study was to investigate the effects of urinary follicle-stimulating hormone (FSH) compounds on the electrical activity of myometrium using signal-processing techniques. Thirty animals were involved in the experiment. After two successive normal estrous cycles, 15 of these animals were put into three equal subgroups. Group 1 was the control; animals were given solvent. Groups 2 and 3 were treated with Urofollitropin and Menotropin, respectively. The other 15 animals were ovariectomized and subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Investigators also have observed FSHR protein and mRNA expression in nongonadal tissues, including uterus and cervix [29], [30], [31]. In these tissues, FSHR may mediate uterine relaxation, as suggested by FSH's ability to modify electrical signaling in the myometrium, independent of estrogen and progesterone [29]. Padmanabhan and colleagues [34] noted a progressive rise in bioactive serum FSH levels during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators also have observed FSHR protein and mRNA expression in nongonadal tissues, including uterus and cervix [29], [30], [31]. In these tissues, FSHR may mediate uterine relaxation, as suggested by FSH's ability to modify electrical signaling in the myometrium, independent of estrogen and progesterone [29]. Padmanabhan and colleagues [34] noted a progressive rise in bioactive serum FSH levels during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…FSH is secreted from the pituitary and, in females, acts primarily on receptors in the ovaries to stimulate follicle development and synthesis of estrogens. Investigators also have observed FSHR protein and mRNA expression in nongonadal tissues, including uterus and cervix [29], [30], [31]. In these tissues, FSHR may mediate uterine relaxation, as suggested by FSH's ability to modify electrical signaling in the myometrium, independent of estrogen and progesterone [29].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study identified ZEB1 as a key suppressor of genes involved in uterine contraction in both humans and mice [36]. FSH, the ligand recognized by FSHR, is known to modulate the electrical signaling property of the uterine muscle [20]. Thus, the weaker binding of ZEB1 in the presence of the G allele may cause de-repression of FSHR.…”
Section: Resultsmentioning
confidence: 99%
“…Not only antibiotics but also other drugs have been studied in respect to their effects on myometrial dynamics. It has been shown that human menopausal gonadotropin and highly purified urinary FSH supress the myoelectrical signals and provides uterine quiescence [18]. It was also demonstrated that estrogen, progesterone and hCG reduce the frequency of uterine contractions [19].…”
Section: Discussionmentioning
confidence: 99%